Peran Ecobrick dalam Meningkatkan Kesadaran Lingkungan di Kalangan Generasi Muda Desa Jaharun B Kec. Galang - Situmeang, Farid Zaki Zein; Girsang, Farhan Al-Fath; Apridayanti, Lisa; Hasanah, Maulida; Humairoh, Siti; Sirait, Dahlia (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
The waste problem is something that is very familiar, especially in Indonesia where a large population produces large volumes of waste. It is feared that the recent increasing use of plastic in daily life will have a bad impact, because plastic is non-organic waste that is difficult to decompose. Ecobricks are a technique for processing plastic waste which is converted into environmentally friendly materials or also called environmentally friendly bricks. The problem of plastic waste also occurs in Jaharun B Village, Galang District, Deli Serdang Regency, thus encouraging KKN students to recycle plastic waste through ecobric. This activity was carried out by KKN students at Al-Wasliyah Muslim Nusantara University with the aim of helping the community, especially the younger generation, in processing waste in facing the problem of inorganic waste in their environment into a new environmentally friendly material. This activity was carried out with the community, especially teenagers from Jaharun B Village, Galang District, Deli Serdang Regency on 20 July-1 August 2024. The results that will be obtained from implementing this ecobrick are that the people of Jaharun B Village, Galang District will have more in-depth knowledge about plastic, about its dangers. , the impact on the environment whether fast or slow, and how to overcome these problems.